2022
DOI: 10.31083/j.rcm2305160
|View full text |Cite
|
Sign up to set email alerts
|

Change of Fibroblast Growth Factor 21 Level Correlates with the Severity of Diabetic Sensory Polyneuropathy after Six-Week Physical Activity

Abstract: Background: Diabetic neuropathy (DN) is a very frequent microvascular complication of type 2 diabetes mellitus (T2DM). Obesity and physical inactivity are well-known risk factors for T2DM. Fibroblast growth factor 21 (FGF21) is a liver-secreted hormone with several beneficial effects on obesity-related metabolic disorders. We aimed to investigate the effect of short-term physical activity on the levels of FGF21, and its correlation with the severity of peripheral sensory polyneuropathy in T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Interventional studies showed that physical activity significantly improves circulating FGF21. For instance, in obese type 2 diabetic patients with peripheral neuropathy (BMI: 31.6 ± 3.9 kg/m 2 ), 6 weeks of moderately intensive physical activity increased serum FGF21 [ 135 ]. In this study, the change in FGF21 negatively correlated with changes in BMI, improvement of current perception threshold value and TNFα levels, while there was a positive correlation between change of FGF21 and adiponectin.…”
Section: Role Of Novel Hepatokines and Gastrointestinal Hormones In N...mentioning
confidence: 99%
“…Interventional studies showed that physical activity significantly improves circulating FGF21. For instance, in obese type 2 diabetic patients with peripheral neuropathy (BMI: 31.6 ± 3.9 kg/m 2 ), 6 weeks of moderately intensive physical activity increased serum FGF21 [ 135 ]. In this study, the change in FGF21 negatively correlated with changes in BMI, improvement of current perception threshold value and TNFα levels, while there was a positive correlation between change of FGF21 and adiponectin.…”
Section: Role Of Novel Hepatokines and Gastrointestinal Hormones In N...mentioning
confidence: 99%
“…Two studies found that irisin levels increased with 12 weeks of moderate-intensity exercise 3 times a week and 3 weeks of moderate- or high-intensity exercise once a week [25, 33]. One found an increase in FGF21 levels at low to moderate intensity 3 times per week for 6 weeks [30].…”
Section: Resultsmentioning
confidence: 99%
“…One found an increase in FGF21 levels at low to moderate intensity 3 times per week for 6 weeks [30]. RE benefits the expression of some myokines, such as BDNF, irisin, IGF-1, and CATB.…”
Section: Effectivenessmentioning
confidence: 99%